The Use of AI-Based Applications to Enhance Students' Writing Skills in Vocational High Schools: A Systematic Literature Review - Fatmawati; Sultan Baa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The rapid advancement of Artificial Intelligence (AI) technology has catalyzed transformative shifts across the educational landscape, particularly within English as a Foreign Language (EFL) instruction. This study systematically examines the integration and efficacy of AI-based applications in developing the English writing skills of Vocational High School students. Employing a qualitative library research design guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, this study synthesizes empirical evidence, theoretical frameworks, and academic publications spanning from 2015 to 2025. The findings indicate that AI-powered tools—ranging from automated grammar checkers and text generators to adaptive feedback platforms—offer substantial scaffolding during the writing process. These applications significantly improve students' grammatical accuracy, vocabulary acquisition, and syntactic variety, while simultaneously bolstering learning autonomy and motivation. However, the analysis also highlights critical challenges, including potential technology over-reliance, digital divide disparities, and the necessity of aligning generic AI capabilities with the specialized English for Specific Purposes (ESP) demands of vocational curricula. Ultimately, this study underscores that while AI serves as a powerful pedagogical aid, its successful implementation depends on strategic teacher mediation to ensure it enhances, rather than replaces, critical cognitive processing.